Modifiable Risk Factors in High-Risk Groups of Colorectal Cancer Screening: A Cross-Sectional Study with Propensity Score Method - Zhong X; Feng N; Ouyang B; Zhao D; Lei L; Peng J; Peng X (Dove Medical Press, 2023)
Xuan Zhong,1,* Nongping Feng,2,* Binfa Ouyang,1 Dan Zhao,1 Lin Lei,3 Ji Peng,3 Xiaolin Peng1 1Department of Oncology, Injury and Nutrition, Shenzhen Nanshan Center for Chronic Disease Control, Shenzhen, Guangdong Province, People's Republic of China; 2Department of Non-Communicable Disease Prevention and Control, Shenzhen Longgang Center for Chronic Disease Control, Shenzhen, Guangdong Province, People's Republic of China; 3Department of Cancer Prevention and Control, Shenzhen Center for Chronic Disease Control, Shenzhen, Guangdong Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaolin Peng, Department of Oncology, Injury and Nutrition, Shenzhen Nanshan Center for Chronic Disease Control, No. 7, Huaming Road, Nanshan District, Shenzhen, Guangdong Province, People's Republic of China, Tel +86-0755-26640203, Email 25731738@qq.comAim: The rising incidence and death rate of colorectal cancer (CRC) have posed a severe danger to the lives and health of residents. Individuals at high risk of CRC are drawing growing attention as the majority of the population impacted by CRC. Hence, it is imperative to examine the detection rates and modifiable factors affecting the populations at high risk for CRC in Shenzhen.Methods: The multi-stage stratified cluster sampling method was used to select residents aged 45- 74 years old from September 2020 to December 2021. The community-based CRC screening was attended by a total of 30,921 residents from urban and suburb regions. The association between modifiable risk factors and the detection rate of high-risk groups was analyzed using multinomial logistic regression with the inverse probability treatment weighting (IPTW) based on the propensity score.Results: The cross-sectional analysis included 24,613 people after excluding 6308 people who had missing or invalid fecal occult blood test (FOBT) results. The detection rate for high-risk groups during CRC screening was 28.50%. Higher rate of high-risk groups was detected among those who were male, aged 60 or above, college or above, other marital status, and living in urban (P < 0.05). Demographic characteristics after IPTW showed a weak correlation coefficient with the detection rate of CRC high-risk both in high-risk and general-risk groups (SMD < 0.1), suggesting a balanced group of participants. The results of logistic regression with IPTW indicated that smoking, drinking, obesity, lack of exercise, vegetable or fruit eating infrequently, red meat, processed meat, cereal food and their clustering status were more inclined to be risk indicators of CRC (P < 0.05).Conclusion: The detection rate for high-risk CRC groups was comparatively high in Shenzhen. The distribution characteristics of lifestyle and dietary risk factors of high-risk groups should be given consideration when adopting individualized intervention measures and comprehensive prevention and control strategies.Keywords: modifiable risk factors, colorectal cancer, high-risk group, propensity score method